The study features of test procedures of students’ knowledge on the physical training lessons - Korobejnik, V.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim is to determine the significance of the relationship and special professional skills necessary to detect and correct errors and evaluating students in physical education classes. The surveys were a group of qualified teachers (n = 31) with different pedagogical experience. Each teacher was asked to arrange the professional quality of the places from 1 to 10. It was found that all investigated have a certain quality and a high level of relationship, but they are manifested in different periods of teaching. It is shown that the process of organizing and carrying out checks of expertise includes logically related mental operations which are the basis of test procedures of students’ knowledge on the physical training lessons. Found that the most weighty qualities were related to skills: a rating, comment exposed estimate visually identify the error and determine its significance.